Effects of Repetitive Transcranial Magnetic Stimulation on Cerebellar Metabolism in Patients With Spinocerebellar Ataxia Type 3 - Chen, Xin-Yuan; Lian, Yan-Hua; Liu, Xia-Hua; Sikandar, Arif; Li, Meng-Cheng; Xu, Hao-Ling; Hu, Jian-Ping; Chen, Qun-Lin; Gan, Shi-Rui (Frontiers in Aging Neuroscience, 2022)
Background Spinocerebellar ataxia type 3 (SCA3) is the most common autosomal dominant hereditary ataxia, and, thus far, effective treatment remains low. Repetitive transcranial magnetic stimulation (rTMS) can improve the symptoms of spinal cerebellar ataxia, but the mechanism is unclear; in addition, whether any improvement in the symptoms is related to cerebellar metabolism has not yet been investigated. Therefore, the purpose of this study was to investigate the effects of low-frequency rTMS on local cerebellar metabolism in patients with SCA3 and the relationship between the improvement in the symptoms and cerebellar metabolism. Methods A double-blind, prospective, randomized, sham-controlled trial was carried out among 18 SCA3 patients. The participants were randomly assigned to the real stimulation group (n = 9) or sham stimulation group (n = 9). Each participant in both the groups underwent 30 min of 1 Hz rTMS stimulation (a total of 900 pulses), differing only in terms of stimulator placement, for 15 consecutive days. To separately compare pre- and post-stimulation data (magnetic resonance spectroscopy (MRS) data and the International Cooperative Ataxia Rating Scale (ICARS) score) in the real and sham groups, paired-sample t-tests and Wilcoxon’s signed-rank tests were used in the analyses. The differences in the ICARS and MRS data between the two groups were analyzed with independent t-tests and covariance. To explore the association between the changes in the concentration of cerebellar metabolism and ICARS, we applied Pearson’s correlation analysis. Results After 15 days of treatment, the ICARS scores significantly decreased in both the groups, while the decrease was more significant in the real stimulation group compared to the sham stimulation group (p < 0.001). The analysis of covariance further confirmed that the total ICARS scores decreased more dramatically in the real stimulation group after treatment compared to the sham stimulation group (F = 31.239, p < 0.001). The values of NAA/Cr and Cho/Cr in the cerebellar vermis, bilateral dentate nucleus, and bilateral cerebellar hemisphere increased significantly in the real stimulation group (p < 0.05), but no significant differences were found in the sham stimulation group (p > 0.05). The analysis of covariance also confirmed the greater change in the real stimulation group. This study also demonstrated that there was a negative correlation between NAA/Cr in the right cerebellar hemisphere and ICARS in the real stimulation group (r = − 0.831, p = 0.02). Conclusion The treatment with rTMS over the cerebellum was found to induce changes in the cerebellar local metabolism and microenvironment in the SCA3 patients. The alterations may contribute to the improvement of the symptoms of ataxia in SCA3 patients.